2022
DOI: 10.3390/agriculture12020207
|View full text |Cite
|
Sign up to set email alerts
|

Green Payment Programs and Farmland Prices—An Empirical Investigation

Abstract: Research has examined the impact of green payment programs on agricultural and economic outcomes such as agricultural productivity and farm income. However, it is unclear whether these policies are capitalized into farmland prices. This paper provides some of the first evidence on the causal impact of green payment programs on farmland prices based on evidence from Taiwan. Using administrative farmland transactions data with the ordinary least squares (OLS) method and the semi-parametric smooth coefficient mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Abdulkarim and David (2016) explored the use of green payments as a perspective of market auctions to reduce energy consumption and lower system delays more than non-green payments, which can effectively reduce environmental pollution from energy consumption. Lee et al (2022) found in their study that farmers using green payment in agricultural production can achieve incentives similar to the US conservation area program, effectively reducing the pressure on environment and climate change. In the domestic society, as early as in 2007, as a third-party financial service provider, EPROPay first advocated the concept of "green payment, happy life".…”
Section: Literature Reviewmentioning
confidence: 99%
“…Abdulkarim and David (2016) explored the use of green payments as a perspective of market auctions to reduce energy consumption and lower system delays more than non-green payments, which can effectively reduce environmental pollution from energy consumption. Lee et al (2022) found in their study that farmers using green payment in agricultural production can achieve incentives similar to the US conservation area program, effectively reducing the pressure on environment and climate change. In the domestic society, as early as in 2007, as a third-party financial service provider, EPROPay first advocated the concept of "green payment, happy life".…”
Section: Literature Reviewmentioning
confidence: 99%